Application of the Growth Inhibition Test to Spiroplasma Taxonomy - WHITCOMB, R. F.; TULLY, J. G.; McCAWLEY, P.; ROSE, D. L. (International Journal of Systematic and Evolutionary Microbiology, 1982)
A total of 33 triply cloned Spiroplasma strains were studied by the conventional growth inhibition test on M1A or M1D agar plates. Sera were prepared to 17 of the isolates, representing five major groups and the four subgroups (subgroups 1-1, 1-2, 1-3 and 1-4) of the Spiroplasma citri complex. Zone sizes varied with the titer and the growth rate of the spiroplasma cultures used as antigens. Test results were standardized by recording zone widths that developed on plates inoculated with cultures containing about 105 colony-forming units per ml. Zone widths in homologous tests ranged from 5 to 19 mm, but were usually at least 10 mm for all but the fastest growing spiroplasmas. Nonspecific zones 1 to 4 mm in width were observed rarely in heterologous crosses between major serogroups, but were characteristic of certain individual strain-antibody combinations and were not observed when other strains of the group or subgroup were examined. Heterologous reactions resulting in zones 2 to 15 mm wide among the four subgroups of the S. citri complex (group I) were observed; such partial reactions were characteristic of all strains within each subgroup. Deoxyribonucleic acid hybridization experiments have shown that major Spiroplasma groups are distinct and can be considered to be putative species. Therefore, growth inhibition serology apparently functions in the Spiroplasmataceae as a test applicable for differentiation at the species level, as it does in the Mycoplasmataceae.